The threat to the safety of children and young people in the digital context - Anna Hojnor; Marcin Barłoga; Henryk Noga; Rober Sito (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2023)
In today's world, where children are getting earlier and earlier access to technology and the Internet, there are many risks that can affect their safety. Parents and teachers have a key role in protecting children from these risks through appropriate awareness and preventive measures. This article discusses the risks faced by children and adolescents in a digital context, based on the results of various studies. A number of risks are presented, such as contact with strangers, cyberbullying, inappropriate online content and technology addiction.